The voluntary declaration in the tax legislation in UAE: A comparative study - Idelbi, Mona (Journal of Legal Sciences, 2023)
Taxes are   the most important public revenues, especially in the context of state intervention and the transformation of the tax from a mere financial tool only into an economic and social guidance tool. Therefore, all countries are keen to preserve this revenue by creating a clear legal system on tax assignment and collection mechanisms, and controlling cases of tax evasion.The tax administration applies   several methods to determine the tax base, which differ from one tax to another, and from one tax system to another. The most important of these methods are the tax returns declared by the taxpayers   ,  one of these  methods also  is to determine the tax base directly by the tax administration.But what  about the mistakes  which may be appeared  in this tax returns? how can the taxpayer correct it  to protect himself from the penalties of tax evasion?the tax legislations allowed  the correction, and specify the cases in which this correction can be resorted   under several names, and  show the results of this correction, which differ from one legislation to another, so our research will study  those errors contained in the tax returns and the mechanism Processing and correcting it by the taxpayer or the tax administration and its implications, especially in  UAE legislation, which devoted a special chapter to this subject under the name of "voluntary declaration" As one of the obligations of the  taxpayers, that  the taxpayer submits a request to correct his tax returns, requests for tax refunds, or the tax assessment conducted by the Federal Tax Authority, but this   was marred by several problems which must be discussed, as its name as a voluntary declaration, , and the dates of its submission which  is sometimes unclear, as well as the implications of its submission, which may be inappropriate, in addition to the practical problems that will be resulted  to its application  , which was raised by the UAE judiciary in many cases.